PENGARUH PROMOSI KESEHATAN MELALUI MEDIA VIDEO EDUKASI TERHADAP MOTIVASI IBU DALAM PEMBERIAN IMUNISASI CAMPAK PADA BAYI - Jalil, Subki Abdul; Mauyah, Nizan; Usrina, Nora (Universitas Murni Teguh, 2025)
Measles is a highly contagious disease and is one of the leading causes of death among children worldwide. Tarmizi stated that 12 provinces have designated measles cases as Outbreak (KLB) cases. The more people who are not vaccinated, the greater the risk of infection. In 2021, there were 132 suspected cases, and in 2022, this reached 3,341 cases. This study design uses a quasi-experimental pre-test post-test method with the aim of analyzing the effect of health promotion through educational video media on mothers' motivation in administering measles immunization to infants. The population consisted of mothers with infants, with a sample size of 62 people determined using the Sample Size application with a prevalence of 20%, a significance level of 0.05, and an absolute precision of 0.1. The sampling method used was accidental sampling, involving mothers who came to the Posyandu (Integrated Health Post). Based on the statistical test results using the paired T-test, a p-value of 0.000 was obtained, where p-value < 0.05, indicating that there is an effect of health promotion through educational video media on mothers' motivation in administering measles immunization to infants in the working area of Samudera Public Health Center, North Aceh Regency. It is expected that Samudera Public Health Center should implement effective and sustainable information delivery efforts, such as health education through audio-visual means, distributing posters, distributing leaflets, and installing banners about the measles disease. Abstrak Campak adalah penyakit yang sangat menular dan merupakan salah satu penyebab utama kematian pada anak-anak di seluruh dunia. Tarmizi mengatakan ada 12 provinsi yang menetapkan kasus campak sebagai kasus KLB. Semakin banyak orang yang tidak divaksinasi, semakin besar risiko infeksi. Tahun 2021 terdapat 132 kasus suspek dan tahun 2022 mencapai 3.341 kasus. Rancangan penelitian ini menggunakan metode quasi eksperimen pre test post test dengan tujuan untuk menganalisis pengaruh promosi kesehatan melalui media video edukasi terhadap motivasi ibu dalam pemberian imunisasi campak pada bayi. Populasi adalah ibu-ibu yang mempunyai bayi dengan jumlah sampel 62 orang dengan menggunakan aplikasi Sample Size dimana Prevalensi 20%, tingkat kemaknaan 0,05 dan presisi absolut 0,1. Metode yang digunakan yaitu accidental sampling yaitu ibu-ibu yang datang ke Posyandu. Berdasarkan hasil uji statistik dengan menggunakan uji T-test (berpasangan) menghasilkan nilai p=0,000 dimana nilai p<0,05 berarti ada pengaruh promosi kesehatan melalui media video edukasi terhadap motivasi ibu dalam pemberian imunisasi campak pada bayi di Wilayah Kerja Puskesmas Samudera Kabupatem Aceh Utara. Diharapkan kepada Puskesmas Samudera perlu dilakukan upaya penyampaian informasi yang efektif dan berkesinambungan seperti penyuluhan kesehatan melalui audio visual, membagikan poster, membagikan leaflet dan memasang spanduk tentang penyakit campak.